2012
DOI: 10.1091/mbc.e11-02-0170
|View full text |Cite
|
Sign up to set email alerts
|

Live-cell monitoring of periodic gene expression in synchronous human cells identifies Forkhead genes involved in cell cycle control

Abstract: A periodic luciferase reporter system from cell cycle–regulated promoters in synchronous U2OS cells measures periodic, cell cycle–regulated gene expression in live cells. This assay is used to identify Forkhead transcription factors that control periodic gene expression, and it identifies FOXK1 as an activator of key cell cycle genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 62 publications
1
27
0
Order By: Relevance
“…At this time, the partial dissociation of VprBP from DDB1 and Cul4 (Fig. 5) would enhance its ability to activate FoxM1 (14). Consistent with this prediction, VprBP partially dissociates from CRL4 in mitosis and a mutant version of VprBP that is impaired for DDB1 binding can still activate FoxM1.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…At this time, the partial dissociation of VprBP from DDB1 and Cul4 (Fig. 5) would enhance its ability to activate FoxM1 (14). Consistent with this prediction, VprBP partially dissociates from CRL4 in mitosis and a mutant version of VprBP that is impaired for DDB1 binding can still activate FoxM1.…”
Section: Discussionsupporting
confidence: 56%
“…FoxM1 activity peaks in G 2 /M phase, consistent with its role in dictating mitotic gene expression, and several kinases have been implicated in its activation (6,(14)(15)(16)(17)(18). FoxM1 is repressed by an intramolecular interaction with its amino-terminal domain, and this inhibition is relieved by cyclin-dependent kinase (CDK) phosphorylation (19).…”
mentioning
confidence: 87%
“…Classical regulators include the transcription factors E2F1 and FOXM1 that are required for the temporal control of gene expression in G1-S and G2-M stages of cell cycle, respectively [4,[19][20][21]. Given that many of the 1 182 genes identified in this study have not been previously observed as being periodic, we sought to discover novel regulatory mechanisms underlying periodic gene expression.…”
Section: Systematic Analysis Of Periodic Gene Promotersmentioning
confidence: 99%
“…Flow cytometry has been broadly utilized for the analysis of biological processes at the single cell level, such as gene expression, cell cycle, apoptosis, and signaling through phosphorylation [37][38][39][40][41][42][43] .The stable expression of fluorescent protein genes in mammalian cells has further enhanced the utility of flow cytometry for cell analysis 38,44 and ligand-receptor interactions 45 . Enhanced capabilities have allowed flow cytometry to become a widely utilized methodology for high-throughput and high-content screening 46 .…”
Section: Introductionmentioning
confidence: 99%